Land rights needed for agricultural development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Susan Bamuh, President of the National Association of Professional Media Women in Cameroon discusses the importance of women being able to inherit and own land.